2019
DOI: 10.1029/2019gb006300
|View full text |Cite
|
Sign up to set email alerts
|

Regional Characteristics of the Temporal Variability in the Global Particulate Inorganic Carbon Inventory

Abstract: Confidential manuscript revised for Global Biogeochemical Cycles 2 • Average global PIC turnover rate is estimated to be on the order of 7 days. • The Great Calcite Belt region strongly influences the seasonal and interannual variability of the global PIC standing stock.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0
3

Year Published

2020
2020
2025
2025

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 62 publications
0
14
0
3
Order By: Relevance
“…When the food vacuole pH is not buffered by high CaCO 3 concentrations, microzooplankton grazing may drive a high proportion of CaCO 3 production being dissolved within microzooplankton food vacuoles in the surface ocean. Previous studies highlighting relatively rapid (3-18 days) turnover of upper ocean CaCO 3 stocks, both regionally (Balch et al, 1992;Poulton et al, 2006Poulton et al, , 2013, and globally (Balch et al, 2005(Balch et al, , 2007Hopkins et al, 2019), as well as regional comparisons of CaCO 3 production and export (Thomalla et al, 2008), are all supportive of this hypothesis. However, there is also evidence which suggests that grazer digestion would be influenced by a high influx of CaCO 3 .…”
Section: Discussionmentioning
confidence: 74%
“…When the food vacuole pH is not buffered by high CaCO 3 concentrations, microzooplankton grazing may drive a high proportion of CaCO 3 production being dissolved within microzooplankton food vacuoles in the surface ocean. Previous studies highlighting relatively rapid (3-18 days) turnover of upper ocean CaCO 3 stocks, both regionally (Balch et al, 1992;Poulton et al, 2006Poulton et al, , 2013, and globally (Balch et al, 2005(Balch et al, , 2007Hopkins et al, 2019), as well as regional comparisons of CaCO 3 production and export (Thomalla et al, 2008), are all supportive of this hypothesis. However, there is also evidence which suggests that grazer digestion would be influenced by a high influx of CaCO 3 .…”
Section: Discussionmentioning
confidence: 74%
“…A study documenting coccolithophores in the Strait of Magellan found that this group represented a minor fraction of the small-sized phytoplankton (Zingone et al, 2011), but other published studies have not specifically sampled for coccolithophores. The Patagonian shelf on the Atlantic side experiences large E. huxleyi blooms (Poulton et al, 2011;, but satellite observations suggest coccolithophore blooms are of lower intensity in the Pacific waters to the west (Hopkins et al, 2019). These observations raise the question of how coccolithophore communities on the western coast and fjords-channels of Patagonia compare with nearby oceans and to fjord systems in the northern hemisphere.…”
Section: ;mentioning
confidence: 99%
“…A study documenting coccolithophores in the Strait of Magellan found that this group represented a minor fraction of the small-sized phytoplankton (Zingone et al, 2011), but other published studies have not specifically sampled for coccolithophores. The Patagonian shelf on the Atlantic side experiences large E. huxleyi blooms (Poulton et al, 2011(Poulton et al, , 2013, but satellite observations suggest coccolithophore blooms are of lower intensity in the Pacific waters to the west (Hopkins et al, 2019). These observations raise the question of how coccolithophore communities on the western coast and fjords-channels of Patagonia compare with nearby oceans and with fjord systems in the Northern Hemisphere.…”
Section: Introductionmentioning
confidence: 99%
“…A wide range of calcification and growth responses to OA have been reported in laboratory studies of coccolithophores, mostly using the cosmopolitan and most abundant species Emiliania huxleyi (reviewed in Meyer and Riebesell, 2015). With some notable exceptions (e.g., Iglesias-Rodriguez et al, 2008), most culture studies showed reduced calcification rates of E. huxleyi in response to simulated OA, while there is no clear trend on growth rates. In a mesocosm experiment using a Norwegian fjord community, increased pCO 2 levels (> 500 µatm) resulted in lower growth rates of E. huxleyi, preventing it from blooming (Riebesell et al, 2017).…”
Section: Introductionmentioning
confidence: 99%